THE EFFECTS OF ARTIFICIAL INTELLIGENCE USAGE ON STUDENT LEARNING BEHAVIOR AND CRITICAL THINKING SKILLS: CORRELATION STUDY ON STUDENTS’ ACADEMIC WRITING - Handayani, Sri; Kandagasari, Nanan; Dewi, Mutiara Indah Nirmala (English Education Department of STKIP Pasundan, 2026)
This study aimed at examining the impact of artificial intelligence (AI) on students' learning behaviour and critical thinking skills in academic writing. The research background is based on the increasing use of AI technology in higher education, particularly in academic writing activities. This research integrated quantitative and qualitative descriptive methods that aim to describe in depth the use of AI technology in students' academic practices in academic writing activities seen from the tendency of student learning behaviour with AI and students' critical thinking skills in the context of academic writing learning supported by quantitative data. The data were taken using a purposive sampling technique, including 78 students who met the criteria. The research findings show that AI positively contributes to increased learning efficiency, understanding of complex material, and student motivation and independence. There is a positive correlation between AI use and learning behaviour and critical thinking skills, although a tendency toward instant use, which can potentially reduce depth of thought, was also found. Correlations between the variables indicate moderate to high levels of strength. Then, the findings of this research are expected to contribute to designing a pedagogical approach that is adaptive to the digital era that maintains basic educational values such as autonomy of thought, academic ethics, and the development of students' intellectual capacity.